Joseph Klaits, Servants of Satan. The Age of the Witch Hunts - Elia Nathan Bravo (Medievalia, 2016)
Joseph Klaits, Servants of Satan. The Age of the Witch Hunts, Bloomington: Indiana University Press, 1985. 209 pp.